Optical Control of CRISPR/Cas9 Gene Editing - Hemphill, James (J Am Chem Soc, 2015)
The CRISPR/Cas9 system has emerged as an important tool in biomedical research for a wide range of applications, with significant potential for genome engineering and gene therapy. In order to achieve conditional control of the CRISPR/Cas9 system, a genetically encoded light-activated Cas9 was engineered through the site-specific installation of a caged lysine amino acid. Several potential lysine residues were identified as viable caging sites that can be modified to optically control Cas9 function, as demonstrated through optical activation and deactivation of both exogenous and endogenous gene function.